Baseline Descriptors of Urban Overweight/Obese Zulu Women Enrolled in a Weight Loss Intervention, South Africa (P21-034-19) - Kassier, Susanna (Curr Dev Nutr, 2019)
OBJECTIVES: Developing a profile of weight and health status, body image, eating behavior and psychological well-being of urban overweight/obese Zulu women enrolled in a weight loss intervention. METHODS: Body mass index (BMI) and waist-circumference was determined. The prevalence of metabolic syndrome (MetS) was assessed according to the National Cholesterol Education Programme Adult Treatment Panel III (NCEP ATP III) criteria. Total energy intake was calculated, based on a three day estimated food record. Eating behavior, presence of depression, self-esteem and general psychological well-being was assessed with the Three-Factor Eating Questionnaire (TFEQ), Beck Depression Inventory (BDI), Rosenberg Self-esteem Scale (RSES), and General Health Questionnaire (GHQ) respectively. RESULTS: The mean ± SD BMI of the group (N = 99) was 37.79 ± 7.47 kg/m(2). The most prevalent MetS risk factor was central obesity, followed by high blood pressure and low HDL levels. MetS was diagnosed in 24% (n = 18) of the group for whom blood samples were available (n = 75). The majority of participants thought that they were currently overweight, however one in ten thought their weight was normal, with a desired BMI being in the overweight range. Daily energy intake was 83% of the Estimated Average Requirement (EAR) for women aged 19–50 years. Depending on the cut-off used, the level of under-reporting ranged from 17.1 to 39.0%. About a quarter of the sample were depressed, with one in ten having a low self-esteem. There were no significant associations between baseline BMI and depression (BDI), self-esteem (RSQ), general psychological well-being and eating behaviour scores (TFEQ). CONCLUSIONS: Potential barriers to compliance with, and remaining in the intervention included a distorted body image, with an underestimation of body weight being the norm. The frequent consumption of high fat foods, energy dense snacks, and a high energy intake over weekends, was documented. Other potential barriers included a low self-esteem and depression. Baseline screening of body image, eating behavior and psychological well being of those enrolled in a weight loss intervention is recommended to curb attrition. FUNDING SOURCES: University of KwaZulu-Natal, Medical Research Council.